SUSTAINABLE DEVELOPMENT GOALS AND THE CHALLENGES OF RURAL ENTREPRENEURS DURING COVID-19 PANDEMIC - Muhamad Asri Abdullah Kamar; Mohamad Azal Fikry Ali (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The human beings have been facing great challenges during the coronavirus disease (COVID-19) pandemic nowadays. However, the number of research regarding the Sustainable Development Goals (SDG) and challenges of rural entrepreneurs during the COVID-19 pandemic is quite limited. The objectives of this research are to explore the challenge of rural entrepreneurs during the pandemic and to discover the affected SDG by those challenges. This research was done at Rural Community Centre (RCC) of Kampung Jelintoh, Gopeng, Perak, Malaysia. It was the most active RCC in conducting entrepreneurship programmes in 2019. This exploration research utilised qualitative approach which involved an in-depth interview by using a semi-structured interview format. Six entrepreneurs were selected through a non-probability sampling technique - a purposive sampling from the list of rural entrepreneurs. The data were analysed using a thematic analysis method. The results disclosed two main themes of the challenges. The first theme was business operation that comprises operation disruption, decrease in demand, shortage of logistic supply, and operation closure. The second theme involves business finance which includes cash flow problems, unexpected increase in production cost, and no access to economic stimulus package. It is suggested that all types of rural businesses be allowed to: operate normally, ensure the smoothness of logistics supply, be offered with financial aids, reduce the production cost, and create an easy-access entry to economic stimulus package. Nevertheless, the business operations must adhere to the Standard Operating Procedure.